Augmentation index as a predictor of right ventricular dysfunction in coronary artery disease: a cross-sectional study - Arash Rahimi; Babak Geraiely; Hamed Vahidi; Mohammadreza Eftekhari; Ramyar Rahimi Darehbagh; Somayeh Mohammadi; Golrokh Ghaffari; Meysam Khoshavi (BMC Cardiovascular Disorders)
Abstract Background Arterial stiffness is a well-established predictor of cardiovascular events and mortality. However, its relationship with right ventricular (RV) function in patients with coronary artery disease (CAD) remains unclear. We aimed to investigate the association between aortic augmentation index (AIx), a marker of arterial stiffness, and RV dysfunction in CAD patients. Methods In this cross-sectional study, 121 patients with stable CAD or acute coronary syndrome who underwent coronary angiography were enrolled. AIx was measured using radial artery applanation tonometry. Comprehensive echocardiography was performed to assess RV function using conventional and speckle-tracking derived parameters. Multivariable linear and logistic regression analyses were used to evaluate the relationship between AIx and RV function, adjusting for potential confounders. Results Patients with high AIx (> 80%, n = 53) had significantly worse RV systolic function compared to those with normal AIx (≤ 80%, n = 68), as evidenced by lower tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC), RV free wall longitudinal strain (RVLS), and RV systolic velocity (RV S’) (all P < 0.05). AIx correlated negatively with TAPSE (r=-0.421), FAC (r=-0.376), RVLS (r=-0.428), and RV S’ (r=-0.355) (all P < 0.001), and positively with pulmonary artery systolic pressure (r = 0.467, P < 0.001) and pulmonary vascular resistance (r = 0.297, P = 0.001). In multivariable analyses, AIx remained an independent predictor of RV dysfunction (adjusted odds ratio 3.42, 95% confidence interval 1.56–7.51, P = 0.002) after adjusting for age, sex, hypertension, diabetes, dyslipidemia, smoking, left ventricular ejection fraction, and Gensini score. Conclusions Increased aortic stiffness assessed by AIx is independently associated with RV dysfunction in patients with CAD. This association is evident across multiple echocardiographic parameters of RV systolic function and is independent of traditional cardiovascular risk factors, left ventricular systolic function, and the extent of coronary artery disease. Our findings suggest that arterial stiffness may play a role in the development of RV dysfunction in CAD patients and highlight the potential importance of assessing and targeting arterial stiffness in this population.